The Influence of Soldier's Ability and Professionalism on the Performance of the Marine Corps Maritime Potential Staff - Haryanto, Dwi; Ramadhan, Etwin; Jumino, Jumino (Universitas Islam Lamongan, 2023)
The purpose of this study was to analyze the effect of the variable of soldier's ability and professionalism of soldiers partially and simultaneously on the performance of Spotmar Kormar. As for the method carried out by researchers using a qualitative approach. Processing data obtained from questionnaires distributed to 30 respondents and analyzed using linear regression with the help of SPSS 25 program resulted that the ability of soldiers had a positive and significant effect with a value of 0.666. This means that by increasing one or part of and of course all dimensions of the ability of this HR will have an impact on increasing the ability and also on performance. Meanwhile, soldier professionalism has a positive and significant effect with a value of 0.368, meaning that an increase in professionalism will have an impact on increasing performance. While the ability and professionalism of soldiers simultaneously have a positive effect with a value of 0.369.